PLANTS, PLANT EXTRACTS AND PHYTOCHEMICALS FOR MANIPULATING RUMINAL FERMENTATION - Wallace, J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The threat to human health associated with the use of antibiotic and chemical feed additives has prompted legislation in the EU to ban antimicrobial growth promoters (AGP), and has accelerated investigations into plants and their extracts as feed additives. The broad potential of plants and their extracts to replace AGP is illustrated by the progress of an EC Framework 5 project, ’Rumen-up’ and its Framework 6 successor, ’Replace’. The Rumen-up project began with a targetted collection of 500 European plants and their extracts, and partners tested their effects on ruminal proteolysis, protozoa, methanogenesis and lactate production. A success rate of about 5% in terms of positive hits illustrated that phytochemicals have great potential as “natural” manipulators of rumen fermentation, to the potential benefit of the farmer and the environment. Some of the positive samples exerted their effect via their essential oils or saponins content. The mode of action of these phytochemicals is at least partially understood. Dietary inclusion of a commercial blend of essential oil compounds significantly decreased NH3 production from amino acids in ruminal fluid taken from sheep and cattle. This effect was mediated partly by effects on ammonia-producting bacteria. Saponins-containing plants and their extracts suppress the bacteriolytic activity of rumen ciliate protozoa, thereby enhancing total microbial protein flow from the rumen. The Rumen-up project also highlighted potentially useful plants which had a benefit that could not be explained by our present knowledge of the effects of phytochemicals on ruminal microorganisms.